IMPROVING STUDENT’S ACTIVITY IN LEARNING CHEMISTRY THROUGH HOMEWORK OF MAKING QUESTIONS - Kartawan, I Made Arya (Universitas Pendidikan Ganesha, 2017)
This study aims to improve student's activity in learning chemistry at SMAN XI-MIPA1 semester odd SMAN 2 Singaraja in the school year 2015/2016. This study included a type of classroom action research with a research cycle model adopted from the Kemmis & Taggart model. As the subject of this class action research is all students of class XI-MIPA 1 odd semester SMA Negeri 2 Singaraja AcademicYear 2015/2016. The data was collected through observation and student questionnaires. Analyze data using descriptive-qualitative, ie by describing the average number of students who ask at each cycle. The results showed that giving the task of making inquiries at home can increase students' activity in the classroom. This student activity can be seen from the number of students who ask questions in the class. The number of students who asked at the time of observation before the action was about 16.67%. After the action, the number of students who ask in cycle I is 41.67% while in cycle II is 53.13%. Thus the method of providing home duties in the form of making the questionable to increase the activity of learning in the classroom.